2016
DOI: 10.15243/jdmlm.2016.034.659
|View full text |Cite
|
Sign up to set email alerts
|

Environmental adaptability of Canavalia virosa and Flemingia congesta to sandy ash soil of Merapi Volcano, Java

Abstract: Studies on volcanic ash of Mount Merapi erupted in 2010 are limited to only characterization of mineralogical, physical, chemical, and biological properties of the volcanic ash. In order to speed up rehabilitation of soils affected by the volcanic ash, it is necessary to study the application of suitable plant species, which is called bio-mechanic conservation. The purpose of this study was to test the environmental adaptability of Canavalia virosa and Flemingia congesta in sandy soil covered by volcanic ash o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…The particle size distribution composition at the four research sites was dominated by sand, while the clay was the lowest fraction of soil. This is similar with the study conducted by Wardoyo and Santosa (2016), which shows that sand has the highest fraction (82.35%) followed by silt (8.78%) and clay (1.62%).…”
Section: F) Distribution Of Soil Particle Sizesupporting
confidence: 91%
“…The particle size distribution composition at the four research sites was dominated by sand, while the clay was the lowest fraction of soil. This is similar with the study conducted by Wardoyo and Santosa (2016), which shows that sand has the highest fraction (82.35%) followed by silt (8.78%) and clay (1.62%).…”
Section: F) Distribution Of Soil Particle Sizesupporting
confidence: 91%
“…Concerning local wisdom possessed by farmers in reclaiming land affected by volcanic eruptions, Ishaq et al (2020) reported that the practice of farmers in reclaiming land after the eruption of Mount Kelud was carried out by mixing volcanic ash with mineral soil underneath by hoeing and adding organic fertilizer (chicken manure or crop residues) and inorganic fertilizers (urea or NPK). In addition, Wardoyo & Santoso (2016) had proven that the use of organic matter as a nitrogen fertilizer improved the growth of Canavalia virosa and Flemingia congesta cultivated in the sandy ash soil of Mount Merapi.…”
Section: Fig 2 Dense and Water-impermeable Layer Sedimented In The mentioning
confidence: 99%